READ FOR PLEASURE AND ACQUIRE THE LANGUAGE - Setiono Sugiharto (Indonesian JELT, 2009)
Despite overwhelming research evidence buttressing the power of reading (Krashen, 2004), reading for pleasure – widely known as Free Voluntary Reading (FVR) – is still excluded in the mandated national curriculum for English language teaching in Indonesia. In fact, critical voices (channeled primarily via scholarly published articles) demanding the inclusion of this kind of reading in the curriculum are almost non-existent. This shows that the power of reading in general and FVR in particular, is not acknowledged by Indonesian scholars, politicians, and language teaching practitioners. This article argues that the sluggish improvement of literacy in this country is due to the fact that English language teaching is geared to conscious learning rather than to acquisition of the language as well as to the exclusive focus on heavy and ‘serious’ literature. This article offers alternative English language pedagogy, one that is not only pleasant for the students, but also helps facilitate literacy development in a powerful way. Implications of this alternative pedagogy are discussed. Keywords:      The power of reading; free voluntary reading; English language teaching; literacy development.